Crop rotation a soil management method for long-term soil productivity - Munther Khazal Salman / Hashim Haneen Kareem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Crop rotation is the rotation of planting for different crops on one plot of land. Crop rotation are important factor for increasing production and improving soil fertility. They are also one of the advantages of modern agriculture, although in the past they have been applied in practice without knowing their principles. Soil  is cultivated with more than one crop in the same year, for example, cultivation with a certain crop type and after harvesting, cultivation with another crop type. This process is useful in the ineffectiveness of the nutrients availability  in the soil, as cultivation of the land with the same crop throughout the year leads to the consumption of the nutrients needed by this crop and thus their effectiveness from the soil, but when using crop rotation that enables the land to recover the nutrients found in the soil, preferably from the legumes.In Iraq crop rotation has been applied in restricted areas which make this system un useful for soil conservation and soil management in most of agricultural lands in the country.